The Relationship between Parenting Styles and Self-Harm Behavior in Early Adolescents in The Agricultural Area of Jember Regency - Oktaviana Dwi Kartikasari; Yeni Fitria; Fitrio Deviantony; Erti Ikhtiarini Dewi; Enggal Hadi Kurniyawan (Nursing and Health Sciences Journal (NHSJ), 2024)
Early adolescents are experiencing various changes in themselves and must adapt to them. In this process, many problems can lead to deviant behavior, one of which is self-harm behavior. Self-harming behaviors can cause harm to oneself and can even lead to suicide. The purpose of this study was to determine the relationship between parenting styles and self-harm behavior in early adolescents in the agricultural area of Jember Regency. This study used a correlational design with a cross-sectional approach. The sampling technique used was proportionate stratified random sampling with 376 respondents. The instruments used were the Parenting Authority Questionnaire (PAQ) and the Deliberate Self-Harm Inventory (DSHI)—data analysis using the contingency coefficient correlation test. The results showed that the most common parenting style was authoritative parenting, with as many as 242 respondents (64.4%), and the most common self-harm behavior was low self-harm, with as many as 319 respondents (84.8%). The correlation test results show that the ρ value is 0.000, which means a significant relationship exists between parenting styles and self-harm behavior in the agricultural area of Jember Regency. Parenting provided by parents ideally or means not restraining too hard and facilitating adolescents to express their opinions can trigger early adolescents' coping mechanisms to be more adaptive by behaving, not deviating, or not committing self-harm behavior. This study can be used as a guideline for schools, mental health nurses, and communities to develop appropriate interventions to address the problem of self-harm and parenting in early adolescents.